Air monitoring for toxic exposures - McDermott, Henry J. (Wiley-Interscience, 2004)
"This book offers ready-to-use information for measuring a wide variety of airborne hazardous materials including chemicals, radon, and bioaerosols. It provides the practical procedures needed for air sampling, collecting biological and bulk samples, evaluating dermal exposures, and determining the advantages and limitations of a given air monitoring method." "Air Monitoring for Toxic Exposures, Second Edition is an accessible resource for nontechnical or student readers, while its depth of coverage ensures its place as the most comprehensive professional reference on the subject available."--Jacket